2013
DOI: 10.1111/raq.12023
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional role of natural productivity and formulated feed in semi‐intensive shrimp farming as indicated by natural stable isotopes

Abstract: The natural productivity of semi-intensively managed shrimp ponds is frequently represented by a high variety of trophic elements that continuously supply nutrients to the farmed organisms. As in the natural ecosystems, these dietary components exhibit differing isotopic signatures at natural abundance levels and since these natural communities belong to different trophic positions and isotopic values of organisms tend to increase with trophic level, the isotopic differences can be measured and used to infer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 77 publications
(122 reference statements)
1
24
0
Order By: Relevance
“…() concluded that enhancing the growth of naturally grown biota in semi‐intensive shrimp ponds significantly improves shrimp yields. These results and those obtained from various studies suggest that shrimp has the ability to filter, ingest and digest natural food present under green‐water culture systems (Anand et al., ; Gamboa‐Delgado, ; Kent et al., ; Roy, Davis, & Whitis, ) reducing their dependency on Met provided by artificial food.…”
Section: Discussionsupporting
confidence: 65%
“…() concluded that enhancing the growth of naturally grown biota in semi‐intensive shrimp ponds significantly improves shrimp yields. These results and those obtained from various studies suggest that shrimp has the ability to filter, ingest and digest natural food present under green‐water culture systems (Anand et al., ; Gamboa‐Delgado, ; Kent et al., ; Roy, Davis, & Whitis, ) reducing their dependency on Met provided by artificial food.…”
Section: Discussionsupporting
confidence: 65%
“…Then, the nutritional value of the biofloc in terms of FA, specially EPA and DHA, is interesting, and the contribution to shrimp nutrition in the grow‐out and pre‐maturation phase could be significant (Ekasari, Crab, & Verstraete, ; Emerenciano et al., ; Martínez‐Córdova, Emerenciano, Miranda‐Baeza, & Martínez‐Porchas, ). Additionally, the digestibility of the food sources could be a relevant factor, and the commercial feed could be less digestible than the biofloc particles (Abreu et al., ; Ekasari et al., ; Gamboa‐Delgado, ), explaining why even its high levels of EPA and DHA are not efficiently incorporated into the muscle in contrast to biofloc (Table ). Therefore, applying such methods (stable isotopes and fatty acids), it has been possible to discern the dietary contribution of multiple food sources to shrimp (Gamboa‐Delgado, ).…”
Section: Discussionmentioning
confidence: 99%
“…As these isotopic differences are substantial and influenced by diet and (or) trophic level, they have been previously employed to distinguish the production method of European seabass (Dicentrarchus labrax), seabream (Sparus aurata), and Atlantic salmon (Salmo salar) (Bell et al 2007;Dempson and Power 2004;Moreno-Rojas et al 2007;Serrano et al 2007). Animals growing in aquaculture systems operating under semi-intensive and intensive rearing conditions derive major proportions of nutrients from the supplied feed, which modifies the animal's isotopic profiles (Nunes et al 1997;Gamboa-Delgado 2014). In this context, the present study examined the use of dual stable isotope analysis as a tentative tool to authenticate samples of Mexican and Ecuadorian shrimp under the hypothesis that the isotopic values of semi-intensively farmed shrimp are influenced by the isotopic signatures of the formulated diets and the pond's natural productivity.…”
Section: Introductionmentioning
confidence: 99%